Generalization of the Hamilton-Jacobi approach for higher-order singular systems - Pimentel, B. M. [UNESP]; Teixeira, R. G. [UNESP] (My University, 1998)
We generalize the Hamilton-Jacobi formulation for higher-order singular systems and obtain the equations of motion as total differential equations. To do this we first study the constraints structure present in such systems.